NILMA LINO GOMES - ENGLISH VERSION - Canavarro Benite, Anna M. (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Professor Nilma Lino Gomes has a degree in Pedagogy from the Federal University of Minas Gerais (UFMG), a Master in Education from the same university and a PhD in Anthropology from the University of São Paulo (USP). Professor Nilma is also a Post-Doctor in Sociology, from the University of Coimbra, and a Post-Doctor in Education from the Federal University of São Carlos (UFSCAR). She is professor Emeritus at the Faculty of Education at UFMG. She was also Minister of the Secretariat of Policies for the Promotion of Racial Equality (SEPPIR), in 2015, and of the Ministry of Women, Racial Equality, Youth and Human Rights, from 2015 to 2016, of the government of the legitimately elected President, Dilma Rousseff.